Meeting Expectations in Management Education Social and Environmental Pressures on Managerial Behaviour (Springer International Publishing, 2018)
This book brings together a variety of international, cross-cultural case studies of management education programmes and discusses the results in light of the present higher social expectations on managerial behaviour. It presents both traditional and unusual approaches to management education, examining concept mapping, transformational learning theory, the practice-theory gap, cultural indoctrination and business students' increased concern with socio-ecological sustainability. It moves from restating the purpose of university business schools to discussing the construction of conducive learning environments on introductory courses and of communities of learning through 'harmonised teaching'. In addressing the social and ethical problems that will soon confront all managers, Meeting Expectations is a valuable resource for teachers, students and practitioners.